Increased Sequence Coverage through Combined Targeting of Variant and Conserved Epitopes Correlates with Control of HIV Replication - Sunshine, Justine; Kim, Moon; Carlson, Jonathan M.; Heckerman, David; Czartoski, Julie; Migueles, Stephen A.; Maenza, Janine; McElrath, M. Juliana; Mullins, James I.; Frahm, Nicole (Journal of Virology, 2013)
A major challenge in the development of an HIV vaccine is that of contending with the extensive sequence variability found in circulating viruses. Induction of HIV-specific T-cell responses targeting conserved regions and induction of HIV-specific T-cell responses recognizing a high number of epitope variants have both been proposed as strategies to overcome this challenge. We addressed the ability of cytotoxic T lymphocytes from 30 untreated HIV-infected subjects with and without control of virus replication to recognize all clade B Gag sequence variants encoded by at least 5% of the sequences in the Los Alamos National Laboratory HIV database (1,300 peptides) using gamma interferon and interleukin-2 (IFN-γ/IL-2) FluoroSpot analysis. While targeting of conserved regions was similar in the two groups (P = 0.47), we found that subjects with control of virus replication demonstrated marginally lower recognition of Gag epitope variants than subjects with normal progression (P = 0.05). In viremic controllers and progressors, we found variant recognition to be associated with viral load (r = 0.62, P = 0.001). Interestingly, we show that increased overall sequence coverage, defined as the overall proportion of HIV database sequences targeted through the Gag-specific repertoire, is inversely associated with viral load (r = −0.38, P = 0.03). Furthermore, we found that sequence coverage, but not variant recognition, correlated with increased recognition of a panel of clade B HIV founder viruses (r = 0.50, P = 0.004). We propose sequence coverage by HIV Gag-specific immune responses as a possible correlate of protection that may contribute to control of virus replication. Additionally, sequence coverage serves as a valuable measure by which to evaluate the protective potential of future vaccination strategies.